AMPLIFICATION AND REDUCTION IN THE MOVIE SUBTITLE ENTITLED 500 DAYS OF SUMMER - Enesia Estrella Sismanto; Dwi Aji Prajoko (Universitas Katolik Widya Mandala Surabaya, 2023)
In subtitling, both reduction and amplification techniques are used even though, theoretically, reduction techniques are preferable because of space efficiency. This research aimed to analyze (1) the amplification techniques and (2) the reduction techniques movie subtitle in the movie entitled 500 Days of Summer. The data collection technique was document analysis. The documents analyzed were the ones containing theories on translation techniques, the English subtitle of 500 Days of Summer and the Indonesian subtitle of 500 Days of Summer. The result was that there were amplification techniques consisting of addition, explicitation, and paraphrase, in which the most dominant technique was explicitation. There were also reduction techniques consisting of implicitation, deletion, and concision, in which the most dominant technique was concision. The number of reduction techniques was more than the number of amplification techniques.Â Keywords: Translation, Translation technique, Reduction, Amplification.